Capaian Pemerintah dalam Pemenuhun Target Sustainable Development Goals (SDGs) Bidang Pendidikan di Kota Jayapura Tahun 2018-2023 - Setiawan, Aria Aditya; Farneubun, Petrus Kanisius (Innovative: Journal Of Social Science Research, 2025)
This research attempts to assess the extent to which government of Jayapura has achieved the target of Sustainable Development Goals (SDGs) in eduction sector in Jayapura. Jayapura dipilih karena sebagai barometer pendidikan di Provinsi Papua. SDGs constitutes a global commitment to realise inclusive development for all children. SDGs consists of 17 goals and this reseach focuses on goals 4, namely ensure inclusive and equitable quality education and promote lifelong learning oppotunities for all. This research employs qualititative methods by analysing primary data sources, such as reports from Central Cureau of Statisics (BPS), National Economic Social Survery (Susenas), international organisations such as the United Nations, and secondary sources including books, journal articles, online articles and othe relevant sources. This research seeks to answer a research question: to what extent has government reached the target of SDGs in education? Indicators used to assess how Jayapura goverment has reached the SDGs target are completion rate and enrolment rate. This research finds that both enrolment and completion rate among school-age children has gradually increased, and this demonstrates that Jayapura government is moving towards the fulfilment of SDGs target in education sector.